âSPINNER PULLING OILâELABORASI PENERAPAN TEKNOLOGI PENGENTAS MINYAK OTOMATIS DALAM PENINGKATAN PRODUKTIFITAS ABON IKAN DI KOPERASI WANITA SRIKANDI, DESA BANTUREJO, KECAMATAN NGANTANG, KABUPATEN MALANG - Nugraha, Muhammad Agung (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Banturejo village is a village in the region Ngantang, Malang regency, East Java, province of Indonesia which has agricultural commodities, livestock and fisheries abundance, as well as close to the tourist sites, namely Selorejo Lake. Fishery commodities is the flagship of the village Banturejo and continue to develop. Besides fish produced from reservoirs, currently there are many citizens who do catfish farming. Catfish are sold directly for consumption and sale around Selorejo Lake. The existence of a superior product for souvenirs can be used as a complement to visitors for souvenirs. Women Cooperative (Kopwan) Heroine is located in the village Banturejo, Ngantang, Malang capture this business opportunity by processing the fish into shredded fish sources. Shredded fish introduced by the consideration that the processed products have a good chance to be a typical souvenirs Selorejo Lake is a high chance. Making shredded fish produced by Heroine Kopwan still using the conventional method is very simple and the result is still a lot of oil content in the floss. In addition, the production capacity of 10 kg of shredded fish is only able to meet 25% of consumer demand.